Revision of the genus Calyxochaetus Bigot (Diptera: Dolichopodidae: Sympycninae) - Runyon, Justin B. (Zootaxa, 2024)
The New World genus Calyxochaetus Bigot (Diptera: Dolichopodidae) is revised and 36 species are recognized, including 14 new species. These species are classified into five species groups as follows: the C. tripilus species group including C. angustipennis (Aldrich, 1901) comb. nov., C. longitarsus sp. nov. and C. tripilus (Van Duzee, 1930); the C. cilifemoratus species group including C. anisoaristus sp. nov., C. arizonicus (Harmston, 1968), C. brooksi sp. nov., C. celatus sp. nov., C. cilifemoratus (Van Duzee, 1924), C. clavicornis (Van Duzee, 1930), C. coloradensis sp. nov., C. distortus (Van Duzee, 1930), C. hardyi (Harmston & Knowlton, 1940), C. harmstoni sp. nov., C. isoaristus (Harmston & Knowlton, 1940), C. luteipes (Van Duzee, 1923) and C. syilx sp. nov.; the C. fortunatus species group including C. cascadia sp. nov., C. fortunatus (Wheeler, 1899), C. leptofortunatus sp. nov., C. oreas (Wheeler, 1899) and C. vegetus (Wheeler, 1899); the C. insolitus species group including C. insolitus (Van Duzee, 1932) and C. pennarista (Harmston & Knowlton, 1940); and the C. frontalis species group including C. binodatus (Harmston & Knowlton, 1940), C. bovanodatus sp. nov., C. desertus sp. nov., C. frontalis (Loew, 1861), C. furcatus (Van Duzee, 1929), C. lamellicornis Parent, 1930, C. lacrima sp. nov., C. nodatus (Loew, 1862), C. ornatus Parent, 1930, C. pictipes (Harmston & Knowlton, 1940), C. remifer sp. nov., C. sobrinus (Wheeler, 1899) and C. tohono sp. nov. The following seven new synonyms are proposed: Calyxochaetus metatarsalis Robinson, 1966 = C. tripilus, syn. nov.; C. millardi Meuffels & Grootaert, 1999 = C. distortus, syn. nov.; C. unipilus (Van Duzee, 1929) = C. furcatus, syn. nov.; C. loewii Parent, 1930 = C. furcatus, syn. nov.; C. patellifer Parent, 1934 = C. ornatus, syn. nov.; C. inornatus (Van Duzee, 1917) = C. sobrinus, syn. nov. and C. hastatus (Van Duzee, 1930) = C. sobrinus, syn. nov. Lectotype designations are made for C. angustipennis, C. frontalis, C. inornatus, C. nodatus and C. vegetus. The known distribution of each species is mapped and a key to males is provided.